Integrated photoanode, preparation method and application thereof and photoelectrode
By growing the SiC active layer in situ on the graphite substrate and forming an integrated photoanode, the problem of interfacial resistance in traditional photoanodes hindering photogenerated charge transmission is solved, and efficient photoelectrochemical water decomposition efficiency and catalytic activity are achieved.
Patent Information
- Application Number
- CN202411853939.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The interface resistance formed by the existing photoanode during the transfer of catalyst material hinders the efficient transmission of photogenerated charges, resulting in low water decomposition efficiency.
Using graphite as the substrate, the SiC active layer is grown in situ on the graphite substrate by chemical vapor deposition to form an integrated photoanode, which improves the conductivity and reduces the interface resistance.
It effectively reduces the interface resistance, promotes the transfer of photogenerated charges at the interface between the SiC active layer and the graphite substrate, and improves the efficiency and catalytic activity of photoelectrochemical water decomposition.
Smart Images

Figure BDA0005191363150000091 
Figure HDA0005191363300000011 
Figure HDA0005191363300000012
Abstract
Description
Technical Field
[0001] The present application belongs to the field of photoelectrocatalysis technology, and specifically relates to an integrated photoanode and its preparation method, application and photoelectrode. Background Art
[0002] Environmental pollution and extreme climate problems seriously hinder the sustainable development of human society. The development and research of hydrogen energy can provide important support for energy conservation and emission reduction. However, the current market share of green hydrogen in the world is still relatively low, and its research and development work needs to be promoted urgently. Using solar energy for photoelectrochemical water decomposition to produce hydrogen is an important green hydrogen production solution. Among them, the effective improvement of the efficiency of photoanode water decomposition is an important guarantee for the commercialization of solar hydrogen production technology. The research and development of efficient photoanodes is on the one hand the design and synthesis of highly active catalyst materials, and on the other hand the innovative design of efficient charge transfer structures of photoanodes.
[0003] The photoanode has a low resistance and stable electrode structure, which is the basis for achieving efficient water splitting characteristics. The current structure of the photoanode is mostly constructed in two steps by synthesizing the catalyst material and transferring it to the conductive glass current collector for bonding. The interface resistance and the bonding problem at the junction of the two phases have always been obstacles to achieving more efficient charge transfer. The integrated photoanode can effectively reduce the interface resistance by directly building the catalyst active material on the current collector material, promote the transfer of photogenerated charge at the interface between the catalyst active material and the current collector, and contribute to the construction of an efficient electrode structure. In related technologies, researchers used hydrothermal method and electrochemical etching method to construct SiC and WO3 integrated photoanodes respectively, fundamentally solving the problem of interface barriers formed by the transfer of catalytic active materials inherent in traditional photoanodes, and realizing the low barrier transmission of photogenerated charge between catalytic active materials and current collectors. However, the SiC current collector has poor conductivity, the metal tungsten sheet is single and cannot be expanded, and the selectivity of the integrated photoanode current collector is severely limited. The current collector material with universal applicability and excellent conductivity is crucial for the integrated photoanode and urgently needs to be developed. Summary of the invention
[0004] This application is based on the inventor's discovery and understanding of the following facts and problems:
[0005] The inventors have found that high-purity graphite has excellent electrical conductivity and thermal stability, and has important applications in semiconductor crystal growth substrate materials based on chemical vapor deposition (CVD). SiC, with its adaptive band gap and excellent semiconductor optoelectronic properties, has shown good application prospects in photoelectrochemical water splitting reaction photoanode materials. Using graphite as a current collector as a substrate, directly growing SiC in situ on a graphite substrate to construct an integrated photoanode can provide a useful reference for the expansion of integrated photoanode current collector materials and the exploration of their corresponding structure-effect mechanism.
[0006] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes an integrated photoanode with universal applicability, good electrical conductivity, and excellent photoelectrochemical water splitting properties, as well as a preparation method, application, and photoelectrode thereof.
[0007] In a first aspect, the present application proposes an integrated photoanode, comprising:
[0008] A graphite substrate, wherein the graphite substrate is composed of high-purity graphite and has a surface roughness within 3.5 μm;
[0009] An active layer, wherein the active layer is disposed on one side surface of the graphite substrate, the active layer is composed of SiC, and the active layer has a loose porous structure;
[0010] The interface resistance of the integrated photoanode is 10Ω to 50Ω.
[0011] The present application uses graphite with excellent conductivity and thermal stability as the substrate, which makes up for the problem of poor conductivity of SiC and improves the conductivity of the integrated photoanode; the active layer is directly grown in situ on the graphite substrate, so that the bonding between the graphite substrate and the SiC active layer is more firmly, which effectively reduces the interface resistance and promotes the transfer of photogenerated charges at the interface between the SiC active layer and the graphite substrate, which is helpful for the construction of an efficient electrode structure; at the same time, the loose and porous active layer enhances the contact area between the electrolyte and the active layer, further improving the photocatalytic water decomposition activity of the integrated photoanode.
[0012] In some embodiments, the thickness of the active layer is 140 μm to 210 μm. If the active layer is too thick, the flow distance of the electrolyte between the SiC pores during the catalytic reaction is too long, which will hinder the flow of generated gas and electrolyte, and is not conducive to the catalytic reaction. On the contrary, if the active layer is too thin, the catalytic active area is too small, which will also lead to low catalytic efficiency. The active layer is within the above thickness range, which is conducive to improving the catalytic efficiency of the integrated photoanode.
[0013] In some embodiments, the active layer is a β-phase single crystal material with a crystallinity of 80% to 90%. Generally speaking, the higher the crystallinity, the better the bulk conductivity of SiC, which is conducive to the directional transmission of photogenerated carriers in the SiC bulk phase.
[0014] In some embodiments, Si and C elements are evenly distributed in the active layer, which indicates the uniformity and continuity of SiC macroscopic growth, further improving the photocatalytic water splitting activity of the integrated photoanode.
[0015] In some embodiments, the mass ratio of Si to C in the active layer is 48:52 to 52:48.
[0016] The second aspect of the present application proposes a method for preparing an integrated photoanode, comprising:
[0017] providing a graphite substrate;
[0018] An active layer is in-situ grown on one surface of a graphite substrate.
[0019] The preparation method is simple to operate and easy to realize industrial production. The obtained integrated photoanode has universal applicability, excellent conductivity and photoelectrochemical water splitting characteristics.
[0020] In some embodiments, the in-situ growth comprises a vapor deposition method, and a raw material of the vapor deposition method comprises trichloromethylsilane, thereby facilitating the formation of a high-quality SiC active layer on the graphite substrate.
[0021] In some embodiments, the in-situ growth temperature of the active layer is 1400°C to 1440°C, and the growth time is 1h to 3h. If the growth temperature is too low, the SiC active layer structure tends to be more dense; conversely, if the growth temperature is too high, the SiC grain size will increase and the catalytic specific surface area of the active layer will decrease. Therefore, a suitable growth temperature is conducive to obtaining a loose and porous active layer structure. The growth time determines the thickness of the SiC active layer, and the preferred growth time is more conducive to obtaining an active layer thickness suitable for the catalytic reaction.
[0022] The third aspect of the present application proposes the use of the aforementioned integrated photoanode in water decomposition to produce hydrogen.
[0023] The fourth aspect of the present application provides a photoelectrode, comprising the integrated photoanode described in the first aspect of the present application or the integrated photoanode prepared by the method described in the second aspect. Thus, the photoelectrode has excellent photoelectrochemical water splitting properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a surface morphology diagram of the SiC active layer in Example 1 of the present application.
[0025] Figure 2 This is a cross-sectional morphology diagram of the SiC active layer in Example 1 of the present application.
[0026] Figure 3 This is a structural diagram of the interface between high-purity graphite and the SiC active layer in Example 1 of the present application.
[0027] Figure 4 This is the XRD spectrum of the SiC active layer in Example 1 of the present application.
[0028] Figure 5 This is the element distribution diagram of the SiC active layer in Example 1 of the present application.
[0029] Figure 6 This is an element spectrum analysis diagram of the SiC active layer in Example 1 of the present application.
[0030] Figure 7 It is a schematic diagram of the structure of the integrated photoanode in Example 1 of the present application.
[0031] Figure 8 This is the element surface distribution diagram of the SiC active layer in Example 1 of the present application.
[0032] Fig. 9 It is a photocurrent density diagram of Examples 1 to 9 of the present application and a comparative example.
[0033] Reference numerals:
[0034] 1-graphite substrate; 2-active layer. DETAILED DESCRIPTION
[0035] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0036] The first aspect of the present application proposes an integrated photoanode, referring to Figure 7 , comprising: a graphite substrate 1, wherein the component of the graphite substrate is high-purity graphite, and the surface roughness of the graphite substrate is within 3.5 μm; an active layer 2, wherein the active layer is arranged on one side surface of the graphite substrate, and the component of the active layer is SiC, and the active layer has a loose porous structure; the interface resistance of the integrated photoanode is 10Ω~50Ω.
[0037] Among them, graphite has excellent electrical conductivity and high temperature stability and is a universal substrate for the growth of crystalline materials. The present application uses graphite as the substrate to make up for the poor electrical conductivity of SiC, and combines the two to improve the electrical conductivity of the integrated photoanode.
[0038] It can be understood that the working principle of the integrated photoanode for water decomposition described in the present application is: in an electrolytic cell, the integrated photoanode acts as an anode, the platinum electrode acts as a cathode, and a loop is formed through an external circuit. Under light conditions, the integrated photoanode material uses the photogenerated carriers generated by the semiconductor photoelectric effect to effectively promote the oxidation reaction process of water on the photoanode and improve the efficiency of the overall water decomposition to generate oxygen and hydrogen.
[0039] In some embodiments, the interface resistance of the integrated photoanode is 10Ω to 50Ω, for example, 10Ω, 20Ω, 30Ω, 40Ω or 50Ω, etc. This can increase the conductivity of the integrated photoanode.
[0040] In some embodiments, the active layer has a loose porous structure. The porous structure of the active layer of one embodiment is as follows: Figure 1 As shown. This increases the contact area between the electrolyte and the active layer, thereby improving the photocatalytic water splitting activity of the integrated photoanode.
[0041] In some embodiments, the thickness of the active layer is 140 μm to 210 μm; in other embodiments, the thickness of the active layer can be 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm or 210 μm, etc.; in some specific examples, the average thickness of the active layer is 187.6 μm. The thickness of the active layer can be measured by a cross-sectional morphology image of a scanning electron microscope. The cross-sectional morphology image of the active layer of an embodiment is as follows: Figure 2 As shown. If the active layer is too thick, the flow distance of the electrolyte between the SiC pores during the catalytic reaction will be too long, which will hinder the flow of the generated gas and electrolyte, and is not conducive to the catalytic reaction. On the contrary, if the active layer is too thin, the catalytic active area will be too small, which will also lead to low catalytic efficiency.
[0042] In some embodiments, the junction between the substrate and the active layer is an integrated structure that is tightly connected. The structure of the junction in one embodiment is as follows: Figure 3 As shown. This effectively reduces the transmission barrier of photogenerated charges between the substrate and the active layer, which is conducive to achieving more efficient charge transfer.
[0043] In some embodiments, the active layer is a β-phase single crystal material with a crystallinity of 80% to 90%, for example, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%. In some specific examples, the crystallinity of the SiC active layer is 83.5%. The crystallinity refers to the proportion of SiC crystal components in the material, which can be measured by XRD spectrum. The XRD spectrum of the integrated photoanode of an embodiment is as follows: Figure 4 Generally speaking, the higher the crystallinity, the better the bulk conductivity of SiC, which is conducive to the directional transmission of photogenerated carriers in the SiC bulk phase.
[0044] In some embodiments, Si and C elements are uniformly distributed in the active layer. The element surface distribution diagram of the integrated photoanode of one embodiment is as follows: Figure 5 and Figure 8 This shows the uniformity and continuity of SiC macroscopic growth, which further improves the photocatalytic water splitting activity of the integrated photoanode.
[0045] In some embodiments, the mass ratio of Si to C in the active layer is 48:52 to 52:48, for example, 48:52, 49:51, 50:50, 51:49 or 52:48. In some specific examples, the mass ratio of Si to C is 51.13:48.87. The element spectrum analysis diagram of the active layer of one embodiment is as follows: Figure 6 shown.
[0046] The second aspect of the present application proposes a method for preparing an integrated photoanode, comprising:
[0047] S1: providing a graphite substrate.
[0048] The graphite substrate may be a high-purity graphite disk, which is cleaned and wiped multiple times and blown clean with argon before use.
[0049] S2: In-situ growth of an active layer on one surface of a graphite substrate.
[0050] In some embodiments, the in-situ growth comprises a vapor deposition method, and a raw material of the vapor deposition method comprises trichloromethylsilane (MTS), thereby facilitating the formation of a high-quality SiC active layer on the graphite substrate.
[0051] As an example, a clean graphite substrate can be placed in a high-temperature chemical vapor deposition furnace, the high-temperature furnace is sealed and closed, the gas in the high-temperature furnace is evacuated, and then the SiC active layer is grown according to the set program. In this way, the SiC active layer can be directly established on the graphite substrate, so that the graphite substrate and the SiC active layer are more firmly bonded, the interface resistance is effectively reduced, and the transfer of photogenerated charges at the interface between the SiC active layer and the graphite substrate is promoted, which is conducive to the construction of an efficient electrode structure.
[0052] In some embodiments, the in-situ growth temperature of the SiC active layer is 1400°C to 1440°C (such as 1400°C, 1410°C, 1420°C, 1430°C or 1440°C, etc.), and the growth time is 1h to 3h (such as 1h, 2h or 3h, etc.). If the growth temperature is too low, the SiC active layer structure tends to be more compact; conversely, if the growth temperature is too high, the SiC grain size will increase and the catalytic specific surface area of the active layer will decrease. Therefore, a suitable growth temperature is conducive to obtaining a loose and porous active layer structure. The growth time determines the thickness of the SiC active layer, and the preferred growth time is more conducive to obtaining an active layer thickness suitable for the catalytic reaction. At the above growth temperature and time, it is conducive to forming a porous SiC active layer on a graphite substrate.
[0053] It should be noted that after the SiC active layer is in-situ grown on the graphite substrate, it needs to be cut into the required size using a diamond cutting machine, such as 20mm×10mm×3mm in length, width and thickness, and then encapsulated with transparent glue to make an electrode for subsequent testing.
[0054] The above method of the present application utilizes silicon-containing raw materials to directly grow the active layer in situ on the graphite substrate, so that the graphite substrate and the SiC active layer are more firmly bonded, the interface resistance is effectively reduced, and the transfer of photogenerated charges at the interface between the SiC active layer and the graphite substrate is promoted, which is conducive to the construction of an efficient electrode structure.
[0055] The third aspect of the present application proposes the application of the aforementioned integrated photoanode in water decomposition and hydrogen production. Specifically, the embodiment of the present application uses a xenon lamp to simulate sunlight, uses the integrated photoanode as the anode, and platinum as the cathode to perform a photoelectrochemical water decomposition test, thereby oxidizing the oxygen element in the water molecule into oxygen and precipitating hydrogen at the cathode. Thus, the integrated photoanode can be applied to the field of water decomposition and hydrogen production.
[0056] The fourth aspect of the present application provides a photoelectrode, including the integrated photoanode described in the first aspect of the present application or the integrated photoanode prepared by the method described in the second aspect. The photoelectrode has all the advantages of the integrated photoanode described above, which will not be repeated here.
[0057] The embodiments of the present application are described in detail below.
[0058] Example 1
[0059] (1) After the surface of the high-purity graphite disk is cleaned and wiped several times and purged with argon gas, it is placed in a high-temperature chemical vapor deposition furnace, the high-temperature furnace is sealed and closed, and the gas in the high-temperature furnace is vacuumed;
[0060] (2) Using trichloromethylsilane (MTS) as the raw material and hydrogen as the carrier gas, the feed rate of MTS was controlled by controlling the ratio of MTS / H2 (2.5:1) and the hydrogen flow rate (20 slm);
[0061] (3) According to the set SiC growth program, the growth temperature was set to 1420°C and the growth time was continued for 2 hours. After cooling down, the sample was taken out and the SiC active layer grown on the high-purity graphite disk was cut into a size of 20 mm × 10 mm × 3 mm using a diamond cutting machine, and then encapsulated with transparent glue to make an integrated photoanode.
[0062] Example 2
[0063] Compared with Example 1, the difference is that the growth temperature in the high temperature furnace is set to 1400°C.
[0064] Example 3
[0065] Compared with Example 1, the difference is that the growth time is 1 hour.
[0066] Example 4
[0067] Compared with Example 1, the difference is that the growth time is 3 hours.
[0068] Example 5
[0069] Compared with Example 1, the difference is that the growth temperature in the high temperature furnace is set to 1440°C.
[0070] Example 6
[0071] Compared with Example 1, the difference is that the growth temperature in the high temperature furnace is set to 1370°C.
[0072] Comparative Example
[0073] The individually grown silicon carbide was transferred to a graphite current collector to assemble the photoanode.
[0074] The characterization data and effect data of the products of the embodiments and comparative examples are as follows:
[0075] Table 1 Test results
[0076]
[0077] The interface resistance of the photoanode of the embodiment and the comparative example was tested by electrochemical AC impedance test. The interface resistances of the integrated photoanode of Examples 1 to 6 were 11.77Ω, 14.75Ω, 24.36Ω, 21.51Ω, 49.20Ω and 68.36Ω, respectively, and the interface resistance of the comparative photoanode was 2105.0Ω. This shows that the present application reduces the interface resistance by in-situ growth of SiC on a graphite substrate, and realizes the low barrier transmission of photogenerated charge between the catalytic active material and the current collector.
[0078] As the key data of the photoelectrochemical water splitting test, the photocurrent density curve was obtained using the linear voltammetric scanning method (LSV) in the electrochemical workstation. The test adopted a three-electrode system (counter electrode: platinum electrode; reference electrode: Ag / AgCl; working electrode: silicon carbide photoanode). The electrolyte was 0.5M Na2SO4 solution, and the light power at the photoanode was set to 100mW / cm 2 The comparison of the photocurrent density curves of the embodiment and the comparative example is as follows: Fig. 9 As shown in Figure 2, it can be seen that the loose porous SiC in Examples 1 to 5 has a higher photoelectrocatalytic water splitting activity, with the starting potentials (vs RHE) being 0.68 V, 0.31 V, 0.17 V, 0.68 V and 0.64 V, respectively, and the highest photocurrent density reaching 2.27 mA / cm 2, 1.98mA / cm 2 , 1.76mA / cm 2 , 2.03mA / cm 2 and 1.54mA / cm 2 The starting potential of the dense SiC photoanode sample in Example 6 is 0.69 V (vsRHE), and the maximum photocurrent density is 1.01 mA / cm 2 , while the starting potential of the comparative photoanode is 0.71 V (vs RHE) and the photocurrent density is 0.33 mA / cm 2 .
[0079] The integrated photoanode was cut into a size of 10mm×10mm×3mm for morphology and composition characterization. The analysis showed that the transmission barrier of photogenerated charges between the SiC active layer and the graphite substrate was effectively reduced due to the tight connection between the SiC active layer and the graphite substrate and the excellent conductivity of high-purity graphite; in addition, the loose and porous SiC morphology enhanced the contact area between the electrolyte and the SiC active layer, effectively improving the photocatalytic water splitting activity of the integrated photoanode and synergistically promoting the photoelectrochemical water splitting performance of the integrated photoanode.
[0080] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0081] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. An integrated photoanode, characterized in that: include: A graphite substrate, wherein the graphite substrate is composed of high-purity graphite and has a surface roughness within 3.5 μm; An active layer, wherein the active layer is disposed on one side surface of the graphite substrate, the active layer is composed of SiC, and the active layer has a loose porous structure; The interface resistance of the integrated photoanode is 10Ω to 50Ω.
2. The integrated photoanode according to claim 1, characterized in that: The thickness of the active layer is 140 μm to 210 μm.
3. The integrated photoanode according to claim 1, characterized in that: The active layer is made of β-phase single crystal material with a crystallinity of 80% to 90%.
4. The integrated photoanode according to claim 1, characterized in that: The Si and C elements are evenly distributed in the active layer.
5. The integrated photoanode according to claim 1, characterized in that: The mass ratio of Si to C in the active layer is 48:52 to 52:
48.
6. A method for preparing the integrated photoanode according to any one of claims 1 to 5, characterized in that: include: providing a graphite substrate; An active layer is in-situ grown on one surface of a graphite substrate.
7. The method according to claim 6, characterized in that The in-situ growth comprises a vapor deposition method, and a raw material of the vapor deposition method comprises trichloromethylsilane.
8. The method according to claim 7, characterized in that The in-situ growth temperature is 1400° C. to 1440° C., and the growth time is 1 hour to 3 hours.
9. Use of the integrated photoanode according to any one of claims 1 to 5 or the integrated photoanode prepared by the method according to any one of claims 6 to 8 in hydrogen production by water decomposition.
10. A photoelectrode, characterized in that: The invention comprises the integrated photoanode according to claim 1 to claim 5 or the integrated photoanode prepared by the method according to any one of claims 6 to 8.